The Student SOM Survey 1995 - SOM Institute, University of Gothenburg (University of Gothenburg, 1997)
This is the third study in the collection of Student-SOM surveys. The aim of these studies is to shed light on opinions and habits of the student generation of today. The questionnaire - mainly a replication of the questionnaire used in Student-SOM 1994 - included questions about study programme, mass media, politics and society, energy, nuclear power and environment, leisure-time activities, and background. Additional questions dealt with the respondent´s opinion on a number of propositions about the development of mass media in Sweden, the cause of violence in society, and if the respondent ever thought of moving to another country. Furthermore the respondents had to state their opinion about a number of proposals put in the environmental debate. Respondents were also asked about their participation in the first Swedish election to the EU-parliament in the fall of 1995. Nonvoters were asked about the reason not to vote, and voters were asked if they used the possibility to vote for a specific person. The question dealing with qualities possessed by two leading politicians, Carl Bildt and Mona Sahlin, was put in two different versions; half of the respondents were asked about sixteen different qualities, while the other half were asked about six different qualities.

Purpose:

To find out how students feel about their education and the social environment at the University of Gothenburg

SOM-institutet har sedan 1993, tillsammans med Göteborgs universitets samhällsvetenskapliga fakultet, genomfört en studentundersökning. Det huvudsakliga syftet med undersökningen har varit att skapa tidsserier där det går att följa hur fakultetens studenter uppfattar sina studier och sin studiesociala miljö. Ett annat syfte är att identifiera studenterna som grupp, med fokus på exempelvis social bakgrund, ålder och bakomliggande orsaker till att de påbörjat sina studier.
Genom dessa tidsserier kan man utläsa trender och trendbrott bland gruppen studenter.

Syfte:

Ta reda på hur studenterna uppfattar sin utbildning och den studiesociala miljön vid Göteborgs universitet
SOM-undersökningen till studenter 1995
Student-SOM 1995
Keywords: CORS; CORS; Higher and further education; Gymnasial och högre utbildning; Media; Media; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap